2002
DOI: 10.1152/ajpgi.00282.2001
|View full text |Cite
|
Sign up to set email alerts
|

Putative effect ofHelicobacter pyloriand gastritis on gastric acid secretion in cat

Abstract: . Putative effect of Helicobacter pylori and gastritis on gastric acid secretion in cat. Am

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…Cats infected with H. pylori ss1 (a nominally cagPAI-positive but functionally cagPAI-inactive nontoxigenic [vacAs2] strain [73]) exhibit transient hypochlorhydria (65), which is analogous to the transient hypochlorhydria reported in the early stages of infection in people (31). Thus, in vivo investigation of the interplay between inflammatory mediators, bacterial products, and gastric function may be facilitated by the cat model of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Cats infected with H. pylori ss1 (a nominally cagPAI-positive but functionally cagPAI-inactive nontoxigenic [vacAs2] strain [73]) exhibit transient hypochlorhydria (65), which is analogous to the transient hypochlorhydria reported in the early stages of infection in people (31). Thus, in vivo investigation of the interplay between inflammatory mediators, bacterial products, and gastric function may be facilitated by the cat model of infection.…”
Section: Discussionmentioning
confidence: 99%
“…In humans it has been reported that gastric acid secretion increases 48 wk after eradication therapy, suggesting that Helicobacter inhibits acid secretion [28] . In cats, acid secretion was inhibited within 3 wk of H. pylori infection [3] . The inhibition of gastric acid secretion may also be accounted for by suppression of histidine decarboxylase (HDC) activity that is important in the pro duction of the major acid secretagogue histamine [5,29,30] .…”
Section: Discussionmentioning
confidence: 99%
“…Cou rillonMallet et al first revealed elevated concentrations of H3R agonist Nαmethylhistamine (NαMH) in the gastric mucosa of H. pylori infected patients [1,5,6] . NαMH has an indirect inhibitory effect on acid secretion by inhibiting the acid secretagogue histamine from the ECLlike ce lls [3,5] . Stimulation of H3Rs on ECLlike cells eventually inhibits histidine decarboxylase (HDC) activity [3,5] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations